Employee motivation, workplace environment and workplace diversity influence on organizational performance: A case of Yamaha Electronic Manufacturing - Mazatul Nadiah, Sahiri (2015)
This research studies the relationship between employee motivation, workplace environment and workplace diversity factors on the organizational performance of a manufacturing firm. The study is conducted at Yamaha Electronic Manufacturing (YEM), which is a Japanese based firms located inIpoh,Perak, Malaysia.The primary objective is to identify the relationship between employee motivation, workplace environment and workplace diversity on organizational performance of YEM. At the same time, this study tries to highlight the current situation at the company in terms of employee motivation, workplace environment and workplace diversity. A quantitative research design were employed and date were collected using survey questionnaires. A total of 161 employees from various department and demographic background were randomly selected as a sample for this study. Upon data analysis, the result shows that all three variables do have a positive significant relationship with organizational performance. Employee motivation and workplace environment have stronger relationship with performance if compared to workplace diversity.